Metabolic fate of dietary volatile compounds in Pieris brassicae - Fernandes, F. (2011)
In this work, the evolution of the qualitative and quantitative profile of the volatile fraction of Pieris brassicae after feeding on Brassica oleracea var. acephala (kale) was monitored through time. HS-SPME/GC-MS was applied to both the host plant and the living insect and its excrements. A total of seventy seven compounds (lipoxygenase pathway by-products, nitrogen compounds, norisoprenoids, sulphur compounds, terpenes, among others) were identified. Thirty eight compounds were identified in insect after 2 h of starvation and forty eight compounds in excrements. Qualitative and quantitative changes were detected along time. Dimethyldisulfide, dimethyltrisulfide, limonene and eugenol were major compounds for all analysed times in both matrices, being limonene an important compound in insect after starvation. The accumulation by P. brassicae of some compounds, such as limonene, was verified, suggesting a mechanism by which the insect can take benefit from bioactive constituents from the diet. Along with accumulation, complete excretion of some compounds, including nitrogen bearing compounds, by-products of glucosinolates was detected. These results reflect one of the strategies used to overcome plant barriers, namely detoxification of toxic compounds. The findings contribute to the knowledge of the metabolization of the volatile compounds in insects and contribute to the body of knowledge of this ecologic system.